Effects of Maternal Coagulation disorder on Birth Weight and Post-Natal Non-Coagulation Problems of Neonates - Ekhtesari, Fatemeh; Moghadam-Banaem, Lida; Shahbazi, Shirin; Shahali, Shadab (Archives of Medical Laboratory Sciences, 2020)
Background: To evaluate the birth weight and post-natal non-coagulation problems of infants of mothers with coagulopathies versus normal mothers. Materials and Methods: In a retrospective cohort study, 100 women with coagulation problems attended the Iranian Haemophilia Comprehensive Care Center, and 200 normal women attending two health centers in Tehran and Karaj, with a history of at least one pregnancy were studied. A questionnaire about mothers’ and neonates’ condition was filled out by an interview, and the data were analyzed using SPSS software, version 16. Results: Using linear regression, the maternal coagulation problem had a negative effect on birth weight (p<0.001, β= -0.31). The prevalence of early and prolonged jaundice in newborns of mothers with coagulopathy was higher than that in newborns of normal mothers (12% vs. 2%, and 7% vs. 3%, respectively), the difference between the two groups in terms of incidence of early jaundice was statistically significant (chi square-p<0.001). The frequency of using phototherapy and blood exchange for treating neonatal jaundice, in neonates of mothers with coagulopathy was higher than in neonates of normal mothers (31% vs. 21% and 8% vs. 21%, respectively) (p<0.001). Furthermore, the duration of hospitalization, hospitalization in NICU, and re-hospitalization during the first month of life in neonates of mothers with coagulation problems was higher than in neonates of normal mothers (p<0.001). Conclusion: Considering the high prevalence of neonatal problems in newborns of mothers with coagulation problems and their lower birth weight, further care measures should be provided for them.